Inflammation response and cytotoxic effects in human THP-1 cells of size-fractionated PM10 extracts in a polluted urban site. (February 2016) - Schilirò, T.; Alessandria, L.; Bonetta, S.; Carraro, E.; Gilli, G.
Abstract: To contribute to a greater characterization of the airborne particulate matter's toxicity, size-fractionated PM10 was sampled during different seasons in a polluted urban site in Torino, a northern Italian city. Three main size fractions (PM10 – 3 μm; PM3 – 0.95 μm; PM < 0.95 μm) extracts (organic and aqueous) were assayed with THP-1 cells to evaluate their effects on cell proliferation, LDH activity, TNFα, IL-8 and CYP1A1 expression. The mean PM10 concentrations were statistically different in summer and in winter and the finest fraction PM<0.95 was always higher than the others. Size-fractionated PM10 extracts, sampled in an urban traffic meteorological–chemical station produced size-related toxicological effects in relation to season and particles extraction. The PM summer extracts induced a significant release of LDH compared to winter and produced a size-related effect, with higher values measured with PM10–3 . Exposure to size-fractionated PM10 extracts did not induce significant expression of TNFα. IL-8 expression was influenced by exposure to size-fractionated PM10 extracts and statistically significant differences were found between kind of extracts for both seasons. The mean fold increases in CYP1A1 expression were statistically different in summer and in winter; winter fraction extracts produced a size-related effect, in particular for organic samples with higher values measured with PM<0.95 extracts. Our results confirm that the only measure of PM can be misleading for the assessment of air quality moreover we support efforts toward identifying potential effect-based tools (e.g. in vitro test) that could be used in the context of the different monitoring programs. Highlights: The PM10 finest fraction (PM < 0.49 μm) was the highest one both in winter and in summer. The particles size influenced both LDH release and IL-8 concentrations. Size-fractionated PM10 extracts induced a significant size-related CYP1A1 expression. Air pollution evaluation should consider the size spectrum of dangerous PM fractions.